Secret honor [videorecording (DVD)] : a film by Robert Altman - Hall, Philip Baker, 1931-; Freed, Donald, 1932-; Stone, Arnold M. (Criterion collection, 2004)
Portrays a disgraced President Richard Nixon recording memoirs in an attempt to defend himself and his political legacy.